Engineering properties of pervious concrete containing palm oil clinker aggregate / Ibrahim Hussein Adebayo - Ibrahim Hussein, Adebayo (2018)
In recent time, frequent flooding has been occurring in major cities around the world due to the combination of increased rainfall and high rate of impermeable surface areas. Pervious concrete is widely accepted as an emerging technology for storm water management. This research was focused on adopting locally available waste material in producing eco-friendly pervious concrete. The aim of this study was to develop pervious concrete containing palm oil clinker (POC) coarse aggregates as an alternative replacement for natural aggregates. Mix proportions were based on four different cement contents at a constant water to cement ratio and cement to aggregate ratio respectively. The effects of mix constituents; aggregate size, cement content and curing method on the properties of the concrete were investigated. Two single-sized grades of aggregates were investigated for POC pervious concrete under three curing methods. The volumetric replacement levels of aggregates with POC were 0%, 25%, 50, 75% and 100%. Engineering properties including compressive strength, porosity, permeability, abrasion resistance and density, as well as sustainability efficiency of the concrete were studied. Generally, increasing the cement content led to increased compressive strength, density and abrasion resistance, while porosity and permeability of the concrete reduced. Meanwhile, the effect of increasing the cement content was marginal compared to the effect of incorporating POC aggregate into the concrete mix. POC aggregate properties such as ACV, L.A abrasion value, shape, size and texture played a vital role in the skeleton structure formation of the concrete. POC being a friable material with pores and irregularly shaped negatively affected the engineering properties of the POC pervious concrete. However, POC pervious concrete mixes containing 9.5mm aggregate sizes showed better engineering properties than the mixes with 12.5mm aggregate size. Since abrasion resistance test is dependent not only on compressive strength and porosity of the concrete but also the surface finishing of the concrete, the surface roughness of POC aggregate influenced the outcome of the POC pervious concrete resistance to abrasion. Furthermore, the effect of curing was minimal on the mechanical properties of the concrete. Curing the concrete in air resulted in about 10% loss in compressive strength due to uncontrolled temperature and humidity condition. However, abrasion resistance of the concrete was improved when full water curing was adopted, whereas air curing method was the least effective. Based on the inter-relationship between the compressive strength, porosity and coefficient of permeability of the POC pervious concrete, optimum mix was identified as 25% POC replacement with POC pervious concrete containing 9.5mm nominal size aggregate. This study concludes that the POC pervious concrete is not suitable for structural application due to its reduced strength. However, it could be acceptable for other applications where the concrete will not be subjected to heavy loads. Incorporation of POC into the concrete mix reduced discharge of CO2 which is dangerous to the environment by 20%.